Sejarah Pemikiran Ekonomi Islam di Masa Rasulullah Saw. - Winarno, Winarno (FAKULTAS SYARIAH DAN EKONOMI ISLAM IAIN SYAIKH ABDURRAHMAN SIDDIK BANGKA BELITUNG, 2017)
Rasulallah Saw. was sent to the earth was carrying the mission that Allah is the almighty and take the mandate to build human civilization more dignified than ever. One form of construction was built by Rasulallah Saw. In order to create a dignified human being from the aspect of the economy. The economic aspect is a form of a right economy that is, protected from things prohibited by syara 'such as manipulation, fraud, corruption and so forth.The history records that, the beginning of Islamic economic thought has actually been done by Rasulallah Saw. and his companions (khulafaurasyidin). The economic problems of the people become very serious concerns because economic problems are the pillars of the faith that must be considered. This is as narrated by Muslims, that Rasulallah Saw. Says